2015
DOI: 10.1128/aem.02180-15
|View full text |Cite
|
Sign up to set email alerts
|

Circulation of Coxiella burnetii in a Naturally Infected Flock of Dairy Sheep: Shedding Dynamics, Environmental Contamination, and Genotype Diversity

Abstract: Q fever is a worldwide zoonosis caused by Coxiella burnetii. Domestic ruminants are considered to be the main reservoir. Sheep, in particular, may frequently cause outbreaks in humans. Because within-flock circulation data are essential to implementing optimal management strategies, we performed a follow-up study of a naturally infected flock of dairy sheep. We aimed to (i) describe C. burnetii shedding dynamics by sampling vaginal mucus, feces, and milk, (ii) assess circulating strain diversity, and (iii) qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 47 publications
8
58
0
Order By: Relevance
“…We also found that the Q fever clinical status was related to the probability of detecting a qPCR‐positive dust swab, this probability being higher in herds with series of abortions attributed to Q fever. This result was expected, since C. burnetii shedding is particularly high after an abortion episode (Guatteo, Beaudeau, Joly, & Seegers, ; Joulie et al., ; Rousset, Berri, et al., ). DNA from C. burnetii was nevertheless detected, sometimes with high bacterial loads, in dust swabs sampled from 19 herds not suspected of Q fever.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…We also found that the Q fever clinical status was related to the probability of detecting a qPCR‐positive dust swab, this probability being higher in herds with series of abortions attributed to Q fever. This result was expected, since C. burnetii shedding is particularly high after an abortion episode (Guatteo, Beaudeau, Joly, & Seegers, ; Joulie et al., ; Rousset, Berri, et al., ). DNA from C. burnetii was nevertheless detected, sometimes with high bacterial loads, in dust swabs sampled from 19 herds not suspected of Q fever.…”
Section: Discussionmentioning
confidence: 69%
“…Dust samples were screened for the presence of C. burnetii DNA by using a multiplex qPCR method targeting both the IS 1111 gene of C. burnetii and an external control (Joulie et al., ). DNA was extracted with the QIAmp DNA kit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of multiple C. burnetii strains within a farm has been reported by several authors using different genotyping methods (SNP analysis, MLVA) (14,17,27). However, the epidemiological and pathological implications of the circulation of different strains are still unknown.…”
Section: Fig 2 Distribution Of the Snp Genotypes In Belgium In Bovinementioning
confidence: 99%
“…Feces of aborting ewes contain up to 10 7 GE of Coxiella per gram [37]. Our in vitro study showed that epithelial cells other than mammary gland epithelium also were capable of internalizing C. burnetii but there was little further propagation of bacterial numbers within the cells.…”
Section: Discussionmentioning
confidence: 88%